Effect of acetamiprid on the immature murine testes. Issue 6 (2nd November 2018) - Terayama, Hayato; Qu, Ning; Endo, Hitoshi; Ito, Masatoshi; Tsukamoto, Hideo; Umemoto, Kanae; Kawakami, Satoshi; Fujino, Yasuhiro; Tatemichi, Masayuki; Sakabe, Kou
ABSTRACT: Neonicotinoids, such as acetamiprid (ACE), a pesticide used worldwide, are believed to be safe for human use. These molecules are structurally similar to nicotine, act as nicotinic acetylcholine receptor (nAChR) agonists, and were shown to be associated with neuromuscular and reproductive disorders, but these experiments were primarily performed in mature animals. In this study, the effects of ACE on the testes of immature mice were examined. The exposure of 3-week-old mice to ACE-containing water for 180 days led to a decrease in body weight and mildly affected spermatogenesis. Additionally, the expression of testosterone-metabolism genes, nAChR subunit genes, and proliferation-associated genes decreased in the testes of ACE-treated mice. Our results show that immature rodents may be less sensitive to ACE than mature ones, that mice may be more likely to accumulate ACE than rats, and that the development of disorders may be affected by the accumulation of ACE in the testes.